Refuge in the Lord : Catholics, presidents, and the politics of immigration, 1981-2013 - McAndrews, Lawrence J. (Lawrence John) (Washington, D.C. : The Catholic University of America Press, 2015)
"In this overarching portrait of three decades of U.S. immigration reform, the author focuses on the roles, on the one hand, of presidents from Reagan to Obama, and on the other, of Catholic immigration advocates, shedding light on the relationship between debates over immigration policy and broader domestic politics"--Provided by publisher.
Ronald Reagan (1981-1989) -- George H.W. Bush (1989-1993) -- Bill Clinton (1993-2001) -- George W. Bush (2001-2009) -- Barack Obama (2009-2013).
Includes bibliographical references and index.
Print version record.
Keywords: United States -- Emigration and immigration -- Government policy -- History -- 20th century; United States -- Emigration and immigration -- Government policy -- History -- 21st century; United States -- Emigration and immigration -- Religious aspects -- History; Presidents -- United States -- History -- 20th century; Presidents -- United States -- History -- 21st century; Catholics -- Political activity -- United States -- History; Religion and politics -- United States -- History; Church and state -- United States -- History; United States -- Politics and government -- 1981-1989.; United States -- Politics and government -- 1989-; Catholics -- Political activity; Church and state; Emigration and immigration -- Government policy; Emigration and immigration -- Religious aspects; Politics and government; Presidents; Religion and politics; United States; SOCIAL SCIENCE / Emigration & Immigration; RELIGION / Religion, Politics & State; History; Electronic books